Ten Years After Bariatric Surgery: Bad Quality of Life Promotes the Need of Psychological Interventions - Galli, Federica; Cavicchioli, Marco; Vegni, Elena; Panizzo, Valerio; Giovanelli, Alessandro; Pontiroli, Antonio Ettore; Micheletto, Giancarlo (Frontiers in Psychology, 2018)
Background: Biliointestinal bypass (BIB) is a surgical bariatric procedure bariatric inducing malabsorption. The aim was to evaluate the clinical situation and quality of life (QoL) ten years after BIB. Ninety patients were contacted for a phone interview [age 41.0 ± 10.6 (mean + SD) years, age-range 31-65 years]. Clinical situation (by ad hoc questionnaire) and QoL (by SF-36) were detected. Methods: Data were analysed with SPSS. BMI dropped from a pre-intervention value of 47.30 ±7.27 to the follow-up value of 31.5±5.81 (p<.001). Results: All patients showed at least one chronic adverse event. At baseline subjects were affected by diabetes (14.4%) and hypertension (40%). A significant (χ² = 18.41; p<0.001) reduction in diabetes (5.6%) as well as a significant (χ² = 50.27; p<.001) reduction in hypertension (32.2%) were found, with percent excess weight loss (%EWL) 59.63 ± 24.60. Thirty-two subjects (35.6%) declared they would not repeat the BIB procedure. Conclusions: BIB showed an overall good clinical outcome (in terms of resolution of hypertension, diabetes and %EWL). However, subjects showed a significant impairment in all domains of SF-36. Ad hoc psychological intervention should be implemented to ameliorate the quality of life of these patients.